Analysis of ICT Competencies Among Distance Learning Students in selected Study Centres of the National Open University of Nigeria - Clifford Moses Amini (Commonwealth of Learning, 2020)
The research evaluated the ICT competencies of Distance learning students of the National Open University of Nigeria, as a pre-requisite for their effectiveness in a computer-based learning environment. 186 students (66 males and 120 females) responded to the questionnaire: Learners’ Competency in the use of ICT (LC in CT), which was adopted from the UNESCO Competency Standard (2008). Results show that distance learning students of the National Open University of Nigeria show competencies in the use of ICT to deepen knowledge. However, only a few can use technology and ICT to create knowledge. This is despite many of the students showing a high level of literacy in computer and technology. The result of hypotheses shows that students’ qualification influences their competency in ICT but their gender never affects ICT competency. The research recommends the strengthening of General Studies (GST) course in computer and technology.